Taxing hazardous waste : the US experience - Hilary Sigman (Rutgers University, Department of Economics, 2003)
Many states in the US impose taxes on hazardous waste. This paper conducts an empirical evaluation of the determinants of these taxes and reviews earlier research on their effects on hazardous waste. Earlier studies have shown that the taxes affect waste management, but my results and other evidence suggest that the tax-induced changes may not have improved welfare. Taxes on industrial hazardous waste are one of the most extensive uses of pollution taxes in the United States. The federal government and many states governments have implemented such taxes. The diversity of hazardous waste taxes makes them an interesting example of pollution taxes because we can compare the responses of polluters to different tax regimes. In this paper, I discuss the existing state and federal hazardous waste taxes and issues in their design and implementation. The paper then presents an empirical analysis of the tax rates adopted by states. In particular, the question is: do these taxes reflect the environmental costs of waste as opposed to other government objectives? Although an earlier study (Levinson, 2003) examines determinants of tax rates, the analysis here expands the hypothesized sources of variation and emphasizes the role of external costs. The results provide some evidence that taxes vary with environmental costs – making it possible that they improve welfare – but also point to non-environmental determinants and much unexplained variation. I then review the literature on the empirical effects of these taxes on pollution and economic behavior. Studies have found only small effects of the state taxes, but these effects indicate that waste generators and managers do respond to the incentives created by taxes. The following section evaluates the advantages and disadvantages of existing taxes on hazardous waste and proposes some alternatives. A final section briefly concludes with an assessment of the U.S. experience with these taxes.
Keywords: 330; Sonderabfall; Ökosteuer; Ländersteuer; Vereinigte Staaten